1941
DOI: 10.2134/agronj1941.00021962003300050008x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐Boron Ratio as an Important Factor in Controlling the Boron Starvation of Plants1

Abstract: C ONSIDERABLE work has been done in investigating the causes of boron starvation in plants in many areas of the United States. Several theories have been proposed and valuable information has been reported concerning the causes of boron starvation in plants.Naftel (8) 3 studied the injurious effect of overliming and was the first to report this to be directly related to boron. He suggested that overliming might increase the growth of micro-organisms, which :in turn would compete with the plants for the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

1949
1949
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 2 publications
0
5
1
1
Order By: Relevance
“…This unexpected behavior of Ca 2+ accumulation might be due to genetic ability of sunflower to cope with salt stress. These data do not support the observations reported by Drake et al (1941), Eck and Campbell (1962), Rengel (1992), Aslam et al (2000) and Ali et al (2001) who stated that a low reduction in yield under saline conditions might be due to a better Ca 2+ /Na + ratio and a high level of Ca 2+ ions which tend to provide relief from other kinds of ion toxicity.…”
Section: Calcium Concentrationcontrasting
confidence: 62%
“…This unexpected behavior of Ca 2+ accumulation might be due to genetic ability of sunflower to cope with salt stress. These data do not support the observations reported by Drake et al (1941), Eck and Campbell (1962), Rengel (1992), Aslam et al (2000) and Ali et al (2001) who stated that a low reduction in yield under saline conditions might be due to a better Ca 2+ /Na + ratio and a high level of Ca 2+ ions which tend to provide relief from other kinds of ion toxicity.…”
Section: Calcium Concentrationcontrasting
confidence: 62%
“…It is well known that application of lime to soils enhances the development of boron deficiency symptoms in boron-deficient soils, but the reason for this is still in doubt. Drake et al (1941) concluded that boron is not adsorbed by clay or organic matter at alkaline pH values, or rendered insoluble by calcium. In contrast the growth of crops in molybdenum-deficient soils is improved by liming, and this is due to increased availability of molybdates with increasing pH.…”
Section: Micronutrientsmentioning
confidence: 99%
“…Boron tolerance of most crops in nonsaline soils is well documented (Reisenauer et al 1973;Gupta et al 1985), but tolerance in saline soils has not been studied as much. Drake et al (1941), Berger (1949) and Fox (1968) observed that high concentrations of Ca, particularly under alkaline conditions, decrease B absorption, implying that more B can probably be tolerated in saline soils, which are rich in Ca and alkaline. The tolerance of wheat to salinity is well known as it is one of the most important crops of saltaffected soils.…”
Section: Introductionmentioning
confidence: 99%